2021
DOI: 10.4103/jfmpc.jfmpc_1425_20
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of male spouse in care during pregnancy in rural areas of district Varanasi

Abstract: Background: Lack of male spouse involvement can affect the delays in the decision to take health care facilities, these are the main contributing factor for increasing maternal mortality and child death ratio. Men involvement in reproductive and sexual health including child health is important in reducing teenage pregnancy, maternal mortality, infant mortality, risky abortions, and total fertility rate. This study aimed to assess the awareness and practices of male spouse in maternal care service… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 10 publications
0
2
1
Order By: Relevance
“…Several studies have revealed that the employment status and the nature of occupation negatively affect the decision of husbands to avail ANC check-ups during their wives' pregnancy (Gibore et al, 2019;Kiptoo & Kipmerewo, 2017;Nyang'au et al, 2021). But in this study, occupation is not found to significantly influence men's decision of availing ANC, which is supported by Singh et al (2021). Men in informal jobs had a low knowledge of ANC, as compared to those who were government or private employees.…”
Section: Discussioncontrasting
confidence: 52%
See 2 more Smart Citations
“…Several studies have revealed that the employment status and the nature of occupation negatively affect the decision of husbands to avail ANC check-ups during their wives' pregnancy (Gibore et al, 2019;Kiptoo & Kipmerewo, 2017;Nyang'au et al, 2021). But in this study, occupation is not found to significantly influence men's decision of availing ANC, which is supported by Singh et al (2021). Men in informal jobs had a low knowledge of ANC, as compared to those who were government or private employees.…”
Section: Discussioncontrasting
confidence: 52%
“…The educational qualification of the male partners is a significant factor that explains increased awareness and ANC check-ups of pregnant wives (Akinpelu & Oluwaseyi, 2014; Chamos et al, 2022; Gnanaselvam et al, 2019; Simkhada et al, 2010; Singh et al, 2021). In the present study, a majority of the participants engaged in the organised sector pointed to a lack of communication between couples as the reason, and those men working as skilled or unskilled labourers and agricultural workers stated that they did not think ANC was required and already had children before as two dominant reasons.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation